Impact of conflict shocks on land rental market dynamics: Panel evidence from Nigeria - Olanrewaju, Opeyemi; Bamiwuye, Temilolu; Omotayo, Abiodun Olusola (Elsevier, 2025)
Access to land is crucial for transforming agri-food systems, promoting market integration, and reducing poverty in sub-Saharan Africa (SSA), where rural land markets are increasingly expanding. However, the escalation of violent conflicts presents serious obstacles to the effective functioning of these land rental markets and their contribution to development objectives. The study employs a household-level panel fixed effects regression model to analyze the impact of violent conflicts and institutional factors on land rental market dynamics, using georeferenced LSMS-ISA and ACLED data. Findings show that conflicts significantly reduce land rental sizes, especially for rural smallholder farmers. Additionally, the study found that institutional factors change how conflict affects land rental markets. The heterogeneous effects revealed that institutional factors reverse the impact of conflict on land rental sizes and values. Specifically, when smallholder women participate in agricultural decision-making in rural areas or when large-scale farming households have access to credit, the typically adverse effect of conflict on land markets transforms into a positive one. Thus, women’s participation in agricultural decision-making and access to formal credit play a crucial role in shaping households' ability to navigate land rental markets in conflict-affected areas. Policymakers can leverage this evidence to develop strategies that improve land access and stability in conflict-prone regions. By understanding household and market dynamics, policymakers can design more effective strategies to promote conflict-sensitive and sustainable agricultural systems and economic stability in Nigeria and other conflict-prone regions.